2020
DOI: 10.1093/fampra/cmaa085
|View full text |Cite
|
Sign up to set email alerts
|

Sleep patterns and physical function in older adults attending primary health care

Abstract: Background Sleep disturbances may contribute to physical function impairment among older adults. Objective To examine the associations between sleep quality and duration and impaired physical function among older adults. Methods Cross-sectional study involving 392 non-institutionalized adults aged ≥65 years, who were recruited from primary health care centres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…33 In the study Arias et al, it was found that the incidence of incontinence over the age of 70 was 30%. 34 These findings are similar to the results obtained in the present study. As stated in the literature, incontinence is a problem that increases in frequency with advancing age and affects individuals in many dimensions.…”
Section: Discussionsupporting
confidence: 92%
“…33 In the study Arias et al, it was found that the incidence of incontinence over the age of 70 was 30%. 34 These findings are similar to the results obtained in the present study. As stated in the literature, incontinence is a problem that increases in frequency with advancing age and affects individuals in many dimensions.…”
Section: Discussionsupporting
confidence: 92%
“…Disabled older individuals are more vulnerable to mental health problems than non-disabled older adults. Previous studies have also discovered that poor sleep quality was associated with functional limitations in older adults [ 16 , 17 ]. This may be that the quality of sleep affects the state of cognitive function and ultimately affects the ability to perform daily living activities.…”
Section: Introductionmentioning
confidence: 99%
“…Following the informed consent process, five assessment tools were administered at baseline and the end of the study. During this assessment process, participants completed the EuroQol 5D-5L (EQ 5D-5L) 37 and Pittsburgh Sleep Quality Index (PSQI) 6 , 38 , 39 under the assistance and supervision of the researchers. Likewise, the researchers filled out Lobo mini-cognitive examination (MCE), 40 , 41 Barthel ADL Index 42 and Tinetti scale.…”
Section: Methodsmentioning
confidence: 99%
“… 4 , 5 In the aging stage, sleep problems are often underdiagnosed, and their prevalence depends on social and environmental factors and daily habits and routines. 2 , 6 Globally, it is estimated that 40%–60% of the older population has poor sleep quality and sleep difficulties. 7 Therefore, sleep problems have become a problem associated with the growing aging phenomenon, 8 , 9 and a relevant public health problem, mainly affecting older people's quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation